(untitled) (LACCEI, 2024)
The control of the operating parameters in the productive process of the ceramics industry allows for reducing process waste and increasing productivity. It can be achieved by transitioning from manual production activities to automated systems. However, this transition is overestimated in costs without a pertinent analysis of the production process’s limitations through engineering tools. In this sense, the present case study evaluates the toilet tanks’ manual manufacturing process. It is determined that the process presents a high volume of defective products and waits for that to limit productivity. Therefore, an automation plan focused on overcoming both limitations through using the Jidoka tool is proposed. Through the implementation of the automated production process (consisting of 5 systems), a positive transition in the production of toilet tanks is verified, and an increase in productivity of 18% is registered compared to the manual process.